2018
DOI: 10.1007/s11067-018-9424-z
|View full text |Cite
|
Sign up to set email alerts
|

Benders Decomposition Algorithms for Two Variants of the Single Allocation Hub Location Problem

Abstract: The hub location problem (HLP) is a special type of the facility location problem with numerous applications in the airline industry, postal services, and computer and telecommunications networks. This paper addresses two basic variants of the HLP, namely the uncapacitated single allocation hub location problem (USAHLP) and the uncapacitated single allocation p-hub median problem (USApHMP). Exact solution procedures based on Benders decomposition algorithm are proposed to tackle large sized instances of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…Hub location problems are firstly proposed by O'Kelly in 1980s [22][23][24]. Typical HLPs can be classified based on their objectives: the p-hub median problems locate p hubs to minimize the total routing cost [25][26][27][28][29][30][31]; the p-hub center problems locate p hubs so that the maximum cost between any OD pair can be minimized [25,32]; and the p-hub covering problems aim to maximize the total flow between all OD pairs covered by p hub facilities [33]. In these studies, the number of hubs to be established, i.e., p, is prespecified.…”
Section: Literature Review: Hub Location Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hub location problems are firstly proposed by O'Kelly in 1980s [22][23][24]. Typical HLPs can be classified based on their objectives: the p-hub median problems locate p hubs to minimize the total routing cost [25][26][27][28][29][30][31]; the p-hub center problems locate p hubs so that the maximum cost between any OD pair can be minimized [25,32]; and the p-hub covering problems aim to maximize the total flow between all OD pairs covered by p hub facilities [33]. In these studies, the number of hubs to be established, i.e., p, is prespecified.…”
Section: Literature Review: Hub Location Problemsmentioning
confidence: 99%
“…In these studies, the number of hubs to be established, i.e., p, is prespecified. Instead of predetermining the number of hubs, some works assume a setup and operation cost for each hub with the objective of minimizing the sum of hub cost and routing cost [29,34] or maximizing the system profit [35]. Comprehensive reviews can be found in Alumur and Kara [36], Campbell and O'Kelly [37], and Farahani et al [38].…”
Section: Literature Review: Hub Location Problemsmentioning
confidence: 99%
“…Therefore, we compare the performance of SPATIAL algorithm (r 25) with state-of-the-art heuristics. We consider three heuristics: (1) the VNS of Ilić et al (2010), (2) Euclidean Projection Method of Meier and Clausen (2017), and (3) Bender decomposition of Ghaffarinasab and Kara (2019). Table 6 provides a comparison in terms of the optimality gap and computational time.…”
Section: Performance On Ap Data Setmentioning
confidence: 99%
“…Proposed solution methodologies range from decomposition-based methods, such as Lagrangian relaxation (Aykin 1994, Pirkul and Schilling 1998, Elhedhli and Hu 2005, branch-and-price (Contreras et al 2011c), and Benders decomposition (de Camargo et al 2009a, Contreras et al 2011a, Ghaffarinasab and Kara 2019 to heuristics, such as genetic algorithms (Topcuoglu et al 2005), tabu search, greedy randomized adapted search procedure (GRASP) (Klincewicz 1992, Mayer andWagner 2002), Variable Neighborhood Search (VNS) (Ilić et al 2010), and Euclidean projection (Meier and Clausen 2017). On the application side, HLPs have been introduced in the context of airline transportation (O'Kelly 1987, Martin andRomán 2004), postal delivery (Ernst and Krishnamoorthy 1996), and telecommunication (Klincewicz 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation